A partial power gradient at coupling region for coupled waveguide fiber - Saktioto, Toto; Ali, Jalil; Zainal, Jasman; Abd. Rahman, Rosly (2008)
Coupled fibers are successfully fabricated by injecting hydrogen flow at 1bar and heating torch flame in the range of 800-1350C. During the fusion process some optical parameters are not clear due to vary. For empirical and theoretical calculation, coupling coefficient and refractive index have been estimated from experimental result of coupling ratio distribution from 1% until 75%. The change in structural and geometrical of fibers affects normalized frequency even for single mode fiber. Coupling ratio as the function of coupling coefficient and separation of fiber axis also changes the normalized frequency at coupling region. The normalized frequency is derived from the radius, the wavelength and the refractive index parameters. Parametric variations are performed on the left and right hand side of the coupling region. At the center of the coupling region, coupling length splits the power to another fiber where the normalized frequency is assumed to be constant. A partial power is modeled and derived using normalized frequency (V), normalized lateral phase constant (u), and normalized lateral attenuation constant, (w) through the second form of modified Bessel function of the l order, which obeys the normal mode, LP01 and normalized propagation constant (b). Total power is maintained constant in order to comply with the energy conservation law. The partial power gradient affected by V, u and w are integrated along z direction coupling region. The model is solved over the pulling length in the range of 7500-9500Î¼m for 1-D where the radial and angle directions were ignored for a scalar magnitude. The core radius of fiber significantly affects normalized frequency and power partially at coupling region rather than wavelength and refractive index of core and cladding. This model can be compared to application of power transmission and reflection of coupled fibers in industrial application.